Individual differences in affective and cognitive processing of musical pitch - Ellison, David (2012)
Musical pitch processing has been studied extensively, but rarely in the context of affective pitch processing, or of individual differences in pitch processing. In this study, participants answered surveys measuring personality and empathy dimensions. They then listened to tonal chord sequences to determine whether they sounded correct or incorrect, and whether they sounded happy or sad, while electroencephalogram (EEG) was recorded. The last chord of each sequence could be either incorrect (containing one note which is out of tune) or correct (containing no such mistuning), and affective content was varied by having sequences resolve in major and minor modes. Personality dimension agreeableness correlated positively with the frequency of musical emotion ratings that agree with music theory. A number of other individual difference variables correlated with EEG amplitudes. Early (300-500ms) electrical brain responses differentiated major-mode, correctly tuned target chords from other target chords. Later (600-800ms, 900-1100ms, 1600-1800ms) electrical brain responses differentiated correctly and incorrectly tuned target chords. This study lends moderate evidence for systematic individual differences in pitch processing. Also, it appears as though the mode of mistuned target chords can modulate brain responses to tuning violations through either sensory or affective processes.